Pupillary light reaction in preclinical Alzheimer's disease subjects compared with normal ageing controls. Issue 7 (11th September 2018) - Van Stavern, Gregory P; Bei, Ling; Shui, Ying-Bo; Huecker, Julie; Gordon, Mae
Abstract : Background/aims: We wished to determine whether the pupillary light reaction can differentiate preclinical Alzheimer's disease (AD) subjects from normal ageing controls. We performed a prospective study evaluating the pupillary light reaction in a cohort of well-characterised subjects with preclinical AD versus normal ageing controls. Methods: We recruited 57 subjects from our institution's Memory and Aging Project, part of our Alzheimer's Disease Research Center. All subjects completed PET-PiB imaging, cerebrospinal fluid analysis and at least 1 neuropsychiatric assessment after their baseline assessment. All participants were assigned a clinical dementia rating and underwent a complete neuro-ophthalmic examination. Participants were divided into a dementia biomarker+ (preclinical AD) and biomarker– (normal ageing) group based on preclinical risk for Alzheimer's dementia. Pupillometry measurements were performed by using the NeurOptics PLR-200 Pupillometer. Results: A total of 57 subjects were recruited with 24 dementia biomarker+ and 33 dementia biomarker- individuals. A variety of pupil flash response (PLR) parameters were assessed. Comparisons between groups were analysed using generalised estimating equations. None of the pupillary parameters showed a significant difference between groups. Conclusions: We found no significant differences in PLR between preclinical AD subjects and normal ageing controls. This suggests that the disease effect on the PLR may be small and difficult to detect at the earliest stages of the disease. Future studies could include larger sample size and chromatic pupillometry.